2018
DOI: 10.1016/j.envsoft.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Bayesian inference in hydrological modeling with a mechanistic emulator

Abstract: As in many fields of dynamic modeling, the long runtime of hydrological models hinders Bayesian inference of model parameters from data. By replacing a model with an approximation of its output as a function of input and/or parameters, emulation allows us to complete this task by trading-off accuracy for speed. We combine (i) the use of a mechanistic emulator, (ii) low-discrepancy sampling of the parameter space, and (iii) iterative refinement of the design data set, to perform Bayesian inference with a very s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The mean function used for all GPEs in this article is the constant zero mean: m 0 ( x ) = 0. Alternatively, the mean could also be set as unknown which is sometimes referred to as ordinary Kriging, as polynomial function (universal Kriging) or any other function like a simplified mechanistic model (e.g., Machac et al, 2018 ).…”
Section: Sequential Design Of Computer Experiments With Exploratormentioning
confidence: 99%
“…The mean function used for all GPEs in this article is the constant zero mean: m 0 ( x ) = 0. Alternatively, the mean could also be set as unknown which is sometimes referred to as ordinary Kriging, as polynomial function (universal Kriging) or any other function like a simplified mechanistic model (e.g., Machac et al, 2018 ).…”
Section: Sequential Design Of Computer Experiments With Exploratormentioning
confidence: 99%
“…For example, Zhang et al (2013) proposed to first identify the posterior region with an optimization method, then build the surrogate model and implement the surrogate-based MCMC simulation; Li & Marzouk (2014) proposed an adaptive approach to find a distribution that is close to the posterior distribution by minimizing the cross entropy, and then construct a locally accurate PCE surrogate therein. Recently, Gaussian process (GP) regression (Rasmussen & Williams, 2006) was combined with MCMC simulation to iteratively refine the surrogate over the posterior distribution (Gong & Duan, 2017;Machac et al, 2018;Zhang et al, 2016;Zhang et al, 2018a). It is shown that this approach can obtain satisfying inversion results with only a small number of high-fidelity model evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…These samples can be viewed as random draws from the approximated posterior distribution. Machac et al (2018) adopted a similar approach to drawing new design points for high-fidelity model evaluations, but they intentionally stretched these samples by a factor of 1.1; that is, the new samples were actually drawn from a distribution that is 1.1 wider than the approximated posterior. Gong and Duan (2017) proposed a more elaborate method to generate representative samples from the approximated posterior, which is implemented as follows: (1) Select the sample with the largest posterior density; (2) divide the converged chain states into several quintile ranges, and select in each range a new sample that has the largest distance to its nearest neighbor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively safe option is to use a surrogate model, or emulator, as a replacement for the UDS model in the RL training to overcome the large computational burden and the low efficiency of data usage (Chua et al, 2018;Kalweit & Boedecker, 2017). Emulators can be divided into two categories: (a) the structure-based methods, which simplify the mathematical structure of the original model for fast computing (Castelletti et al, 2012;Machac et al, 2018), and (b) the data-based methods, which establish an emulator using data generated from planned experiments conducted on the simulation model or the sensor (Bieker et al, 2020;Carbajal et al, 2017;Castelletti et al, 2012). The latter category has better adaptability to different dynamics, and is the focus of this work.…”
mentioning
confidence: 99%